2008
DOI: 10.1016/j.devcel.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase 1 Is a Negative Regulator of Lysosomal Exocytosis

Abstract: SUMMARY Lysosomal exocytosis is a Ca2+-regulated mechanism that involves proteins responsible for cytoskeletal attachment and fusion of lysosomes with the plasma membrane. However, whether luminal lysosomal enzymes contribute to this process remains unknown. Here we show that neuraminidase Neu1 negatively regulates lysosomal exocytosis in hematopoietic cells by processing the sialic acids on the lysosomal membrane protein Lamp-1. In macrophages from Neu1-deficient mice, a model of the disease sialidosis, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
183
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(198 citation statements)
references
References 49 publications
3
183
1
4
Order By: Relevance
“…This conclusion is indirectly supported by our observation of the increased cross-reactivity of MAL-2 lectin specific for sialic acid residues with multiple proteins in the macrophages from Neu1-deficient mice, but further experiments are needed to identify the affected proteins. Also, we cannot rule out the possibility that Neu1 deficiency and/or over-sialylation of the cell surface proteins affects the internalization of phagosomes, considering that Neu1 deficiency has been shown to promote excessive lysosomal exocytosis by increasing the sialylation and decreasing the turnover rate of exocytic receptor LAMP-1 (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is indirectly supported by our observation of the increased cross-reactivity of MAL-2 lectin specific for sialic acid residues with multiple proteins in the macrophages from Neu1-deficient mice, but further experiments are needed to identify the affected proteins. Also, we cannot rule out the possibility that Neu1 deficiency and/or over-sialylation of the cell surface proteins affects the internalization of phagosomes, considering that Neu1 deficiency has been shown to promote excessive lysosomal exocytosis by increasing the sialylation and decreasing the turnover rate of exocytic receptor LAMP-1 (39).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the components of the multienzyme complex, Neu1, CathA, and ␤-galactosidase (or its alternatively spliced elastin-binding form), participate in processing of endothelin-1 (21,33), assembly of the elastic fibers (21,34,35), pro-inflammatory response in macrophages (36), migration, invasion, and adhesion of cancer cells (37), proliferation of aortic smooth muscle cells (38), and exocytosis (39). In humans, genetic defects in CathA cause disruption of the complex and trigger galactosialidosis (MIM 256540), a severe multisystemic disease characterized by combined deficiency of Neu1, ␤-galactosidase, and CathA (for review, see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The low level of donor cell repopulation in the MPS IIIA mouse brain is unlikely to be the result of a defect in mobilization of bone marrow-derived cells from the bone marrow compartment to peripheral blood, as the activity of two serine proteases involved in cellular mobilization was similar in normal and MPS IIIA mice. These proteases, cathepsin G and neutrophil elastase, have been implicated in altered bone marrow progenitor cell retention/mobilization in sialidosis mice (Yogalingam et al 2008). Additionally, no differences in GFP-expressing donor leukocyte reconstitution Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon might also be primarily explained by the impaired lysosomal degradation. However, contribution of enhanced exocytosis is also plausible, since a Neu1 KO mice study revealed that Neu1 negatively regulates exocytosis through desialylation of the lysosomal protein LAMP1 [14]. Whether Neu1 deficiency affects cellular homeostasis by controlling exocytosis is to be explored in the future.…”
Section: Deformed Embryoid Bodies Of Patient-derived Cellsmentioning
confidence: 99%